THE ADOPTION OF BORDER TECHNOLOGY OF IMMIGRATION CONTROL AND AUTOGATES IN INDONESIA - Bagas Hidayat Putra; Ridwan Arifin (LPPM STMIK STIKOM Indonesia, 2020)
There has been no research on border automation or the mechanism of autogate system at airports in Indonesia, including a comparative study on border technology of immigration control in several countries. This paper is to describe how the border technology of immigration control and autogate at airports in Indonesia work and to compare the adoption of border technology of immigration control at airports in four countries. It presents a discussion with a qualitative research method by applying a systematic procedure reviewing or evaluating documents or document analysis. This study finds Border technology in Indonesia has been established with an integrated information system called SIMKIM under the EDAS as a connecting system to every interoperable system at immigration offices, border controls, detention centers, and representative offices overseas. The DGI has deployed an automated border control for Indonesian passport holders at Jakarta International Airport and Bali International Airport, and foreign passport holders from twelve selected countries at the departure terminal of Bali International Airport. For further research, it is essential to evaluate the adoption of border technology of the immigration control process in Indonesia and the evaluation of the deployment of autogate at two airports in Indonesia.